Antioxidant activity test of combination of Centella asiatica leaf extract and mint leaf extract as an alternative herbal drink - A.A. Istri Mas Padmiswari; Nadya Treesna Wulansari; Putu Indrayoni (Jurnal Pijar Mipa, 2023)
Antioxidant compounds are vital for the body. An imbalance in the body's levels of free radicals and antioxidants will cause oxidative stress and cause disease because free radicals will damage the surrounding molecules (lipids, proteins, and nucleic acids), causing damage to tissues and cells. Today many studies are interested in using natural antioxidants in food, beverages, cosmetics, and therapies derived from plants. Centella asiatica is a plant often used as a source of antioxidants because it contains active compounds such as terpenoids, flavonoids, polyphenols, tannins, carotene, and vitamin C, which have antioxidant activity. In addition to containing 78% menthol, mint leaves contain resin and tannins, which are several polyphenolic antioxidants that prevent or neutralize the effects of free radicals. Antioxidants are compounds that can delay, slow down, or inhibit oxidation reactions and fight free radicals. The results showed that the antioxidant activity of the combination of Centela asiatica leaf extract and mint leaf extract based on the results of the analysis showed that it was included in the strong category.